A Semi-Analytical Study on Multiscale Porous Biocatalytic Electrodes in the Enzyme Reaction Process - Vijayalakshmi, V.; Ananthaswamy, V.; Jothi, J. Anantha (Communications in Mathematics and Applications, 2024)
A multiscale porous biocatalytic electrode’s oxidation of glucose is explained theoretically. The model that describes diffusion and response within a hydrogel film is composed by two non-linear differential equations. Approximate analytical findings of the glucose concentrations, current, and the oxidised mediator have been obtained via the new homotopy perturbation technique. Furthermore, an analytical calculation is performed to determine the ideal electrode thickness for the film by employing Ananthaswamy-Sivasankari Method (ASM). It also investigates how parameters affect current. Our approximate analytical expressions are validated by the numerical simulation (MATLAB).